2(2y-3x)+6-7=

Simple and best practice solution for 2(2y-3x)+6-7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2y-3x)+6-7= equation:


Simplifying
2(2y + -3x) + 6 + -7 = 0

Reorder the terms:
2(-3x + 2y) + 6 + -7 = 0
(-3x * 2 + 2y * 2) + 6 + -7 = 0
(-6x + 4y) + 6 + -7 = 0

Reorder the terms:
6 + -7 + -6x + 4y = 0

Combine like terms: 6 + -7 = -1
-1 + -6x + 4y = 0

Solving
-1 + -6x + 4y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + -6x + 1 + 4y = 0 + 1

Reorder the terms:
-1 + 1 + -6x + 4y = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -6x + 4y = 0 + 1
-6x + 4y = 0 + 1

Combine like terms: 0 + 1 = 1
-6x + 4y = 1

Add '-4y' to each side of the equation.
-6x + 4y + -4y = 1 + -4y

Combine like terms: 4y + -4y = 0
-6x + 0 = 1 + -4y
-6x = 1 + -4y

Divide each side by '-6'.
x = -0.1666666667 + 0.6666666667y

Simplifying
x = -0.1666666667 + 0.6666666667y

See similar equations:

| (6t^2+t)(6t^2+t)-8(6t^2+t)+7=0 | | x^2+6.25x+21.5=0 | | z=1+4i | | 9x+12y=237 | | 98-6y+2y=62 | | 3AB=4AC | | 4((49-3y)/2)/2 | | 5/11×4/9 | | 2y-14=16 | | 34=5a-3(2a-7) | | (2n-1)(2n-1)+4(2n-1)-12=0 | | 34=5a+3(2a+7) | | 2*x+5=10 | | 3-log(2x)=1 | | 3-ln(2x)=1 | | y^2+30y+216=0 | | 8x-7w+5x+7y+3y+3w= | | 3*4g=12g | | 3y^2+2xy-x^2=7 | | 4w+2x-y+3w-15x-8y= | | 6x-3y+10w-6y-3w+7x= | | 6(c-1)whenc=6 | | 3w+2y+7x+6x-11y+4w= | | 3w+7x-11y+4w+6x+2y= | | 16(1/2(8)-1) | | 4.9t^2-10.5t-27.3=0 | | 15a+13b+2c+2c-4b-2a= | | x^2-18+48=0 | | 20p+18q+p-4q-7p= | | 3x+5=-7x+12 | | 14m+3n-6m+7n= | | 1/216^2-16 |

Equations solver categories